Insights into genetic and clinical profiles of triple A syndrome in Sudanese children - Musa, Salwa A.; Abdullah, Mohamed A.; Hassan, Samar S.; Streiff, Eliane; Lange, Franziska; Babiker, Omer O.; Ibrahim, Areej A.; Elshafie, Hiba A.; Huebner, Angela; Koehler, Katrin; Quitter, Friederike (Frontiers in Endocrinology, 2025)
IntroductionTriple A syndrome (OMIM*231550) is a rare autosomal recessive disorder characterized by achalasia, alacrima, adrenal insufficiency, and neurological features. It is caused by functional impairment of the nucleoporin ALADIN due to mutations in the AAAS gene. Limited data exists on triple A syndrome from Sub-Saharan African and Arab countries. Our objective is to perform a comprehensive clinical and genetic study in Sudanese patients diagnosed with triple A syndrome.MethodsThe clinical diagnoses were based on characteristic clinical and laboratory findings. Genetic testing was conducted in 20 families, encompassing 31 patients, revealing six different AAAS mutations.ResultsA previously described mutation in exon 9 (c.934C>T) was present in 35%, and the known Arabic founder mutation c.1331+1G>A (intron 14) was found in 30% of the families. In addition, two novel mutations, including an 8 bp-deletion at the exon 4/intron 4 junction (c.394_399+2delCTGTCTGT) and a 1 bp-deletion in exon 9 (c.852delG) were identified. DiscussionGenotype-phenotype analyses highlighted significant variability in symptom occurrence, age of onset, and disease severity. Consistent with the high consanguinity rates in Sudan, most mutations (95%) occurred in a homozygous state. In conclusion, triple A syndrome is likely underdiagnosed in Sudan and exhibits significant variability in phenotypic presentation even among affected individuals within the same family or mutation.